Cross cultural adaptation and validation of Nepali Version of Activity Scale for Kids (ASK) - Regan Shakya; Renuka Suwal; Ishwar Adhikari; Jasmine Shrestha; Subham Gyawali; Archana Shrestha (SpringerOpen, 2022)
Abstract Background Activity Scale for Kids (ASK) is self reported, widely used tool to measure the physical disability in children aged 5-15 years. It has two versions; ASK-performance version and ASK-capability version, both with excellent psychometric properties in English and other translated languages. However, the tool is not available in Nepali. The aim of our study is to translate, culturally adapt and validate the tool in the context of the Nepali population. Methods A standard translation guideline was used to translate both the versions of ASK tool into the Nepali language. One hundred and two participants were assessed to establish the reliability and validity of the tool. Internal consistency and test retest reliability was established using cronbach's alpha and intra class correlation coefficient. Validity was established by three methods; ceiling and floor effects, group discriminations, and comparing the results of ASK with the Nepali version of KINDL. Results The mean age of the sample participants were 12.74 years (SD 2.2). The internal consistency and test retest reliability for both the Nepali versions of ASK was significant at 0.98 and 0.94 respectively. The tool had a negligible ceiling effect (< 5%) but a moderate floor effect (ASKp-Np 7.8% and ASKc-Np 8.8%). It was able to discriminate between the mobility aid required for moving inside and outside the home environment. Moderate correlation was observed between the both the Nepali versions of ASK and the total score of KINDL (r = 0.5). Conclusions Nepali version of ASK is reliable and valid tool to measure physical disability in the Nepali pediatric population.